The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00335-018-9759-2
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of the aged glutathione phenotype is dependent on tissue of origin

Abstract: Glutathione is a ubiquitous antioxidant that protects cells against reactive oxygen species and other chemical stressors. Despite its functional importance, the impact of genetics on the glutathione system has yet to be fully appreciated. Here, we investigated the heritability of glutathione levels and redox status in a disease-relevant condition: advanced age. We assembled a panel of 18-21-month-old mice representing 19 inbred strains and quantified the levels of reduced and oxidized glutathione, and their su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Especially, pyroglutamic acid, glutamic acid, and glutathione are involved in glutathione metabolism and were down-regulated in DSS group. The glutathione pathway is a key hepatic defense mechanism and deactivates reactive metabolites before they have the chance to damage cellular proteins [29]. In addition, we found that tryptophan metabolism was influenced significantly by IBD in our research, shown in Figure 5a.…”
Section: Dss Induced Ibd Cause Perturbations In Liver Metabolismsupporting
confidence: 55%
“…Especially, pyroglutamic acid, glutamic acid, and glutathione are involved in glutathione metabolism and were down-regulated in DSS group. The glutathione pathway is a key hepatic defense mechanism and deactivates reactive metabolites before they have the chance to damage cellular proteins [29]. In addition, we found that tryptophan metabolism was influenced significantly by IBD in our research, shown in Figure 5a.…”
Section: Dss Induced Ibd Cause Perturbations In Liver Metabolismsupporting
confidence: 55%
“…Although there is a great amount of information about glutathione, it is evident that there is still a lot to discover about its function in cellular regulation. In the last years, approaches to design future therapies consider novel aspects as, for example, heritability of GSH levels in different organs/tissues [ 190 ], regulation of epigenetic mechanisms as response to variations of glutathione level or GSH/GSSG ration [ 191 ]; redox signaling through the formation of mixed disulfides stimulated by hormones [ 192 ] or even, testing in animal models, a mitochondrial transplantation therapy that could increase ATP supply and reduce ROS damages [ 193 ]. Indeed, Cowan et al [ 194 ] successfully reported intracoronary exogenous mitochondrial delivery into an ischemic heart for cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…The DSS group was altered in amino acid and protein metabolism, and amino acid-related compounds such as pyroglutamic acid, glutamic acid, and glutathione were involved in glutathione metabolism and downregulated in the DSS group. The glutathione pathway is a key hepatic defense mechanism and deactivates reactive metabolites before they have an opportunity to damage cellular proteins [ 27 ]. In addition, we found that tryptophan metabolism was influenced considerably by IBD in our research.…”
Section: Discussionmentioning
confidence: 99%